2019
DOI: 10.3928/23258160-20190401-14
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Course Following Vitreous Surgery for Epiretinal Membrane

Abstract: BACKGROUND AND OBJECTIVE: To follow the long-term course of visual acuity (VA) and central retinal thickness (CRT) over at least a 3-year follow-up after vitreous surgery in patients with epiretinal membrane (ERM). PATIENTS AND METHODS: This study examined 43 eyes of patients who underwent 23- or 25-gauge vitreous surgery for ERM. RESULTS: There was significant improvement of the VA at 3 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Even in cases with very good pre-operative visual acuity, the treatment results in significant improvement in vision ( 15 ). Significant improvement of visual acuity after PPV for ERM has also been found in the analysis of Kishi et al 3 months after the surgery, which was maintained over the 5-year follow-up period ( 16 ).…”
Section: Discussionmentioning
confidence: 57%
“…Even in cases with very good pre-operative visual acuity, the treatment results in significant improvement in vision ( 15 ). Significant improvement of visual acuity after PPV for ERM has also been found in the analysis of Kishi et al 3 months after the surgery, which was maintained over the 5-year follow-up period ( 16 ).…”
Section: Discussionmentioning
confidence: 57%
“…In our study, patients with pediatric idiopathic ERMs had better preoperative BCVA than that of patients with pediatric secondary ERMs; but better postoperative BCVA improvement were seen in the group of Declarations patients with pediatric secondary ERMs. Many previous studies have shown comparative better preoperative BCVA in pediatric patients with idiopathic ERMs [7,21], and this better preoperative BCVA may be related to mild anatomical macular pathologies especially less EZ band disruptions on OCT [22][23]. We also observed signi cant postoperative VA improvement both for idiopathic and secondary ERMs in children, and these results con rm with that of Ferrone and Chaudhary [24]; but better postoperative BCVA improvement were seen in the group of patients with pediatric secondary ERMs (4.9 lines VS 2.5 lines), possibly because of the acquired longer-term amblyopia caused by idiopathic ERMs, and this result also highlight the importance of early school VA screening to detect and treat pediatric idiopathic ERMs as early as possible.…”
Section: Discussionmentioning
confidence: 90%
“…We found a significant association between metamorphopsia scores and EIFL thickness both before and after surgery. Many previous reports have indicated that visual acuity and metamorphopsia of ERM patients are improved by surgery (Falkner-Radler et al 2010;Kinoshita et al 2012;Bae et al 2013;Kim et al 2013;Okamoto et al 2015;McGowan et al 2016;Kishi et al 2019;Bae et al 2020). In the present study, we also observed significant improvements in visual acuity and metamorphopsia scores both for horizontal lines and vertical lines at 3 months after surgery compared to baseline, but we found no significant correlation between EIFL and visual acuity both before and after surgery.…”
Section: Discussionmentioning
confidence: 97%